6(4-2e)-3(5+3e)=

Simple and best practice solution for 6(4-2e)-3(5+3e)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4-2e)-3(5+3e)= equation:


6(4-2e)-3(5+3e)=0

We simplify the equation to the form, which is simple to understand
6(4-2e)-3(5+3e)=0

Reorder the terms in parentheses
+(+24-12e)-3*(5+3e)=0

Remove unnecessary parentheses
+24-12e-3+*(+5+3e+)=0

Reorder the terms in parentheses
+24-12e+(-15-9e)=0

Remove unnecessary parentheses
+24-12e-15-9e=0

We move all terms containing e to the left and all other terms to the right.
-12e-9e=0-24+15

We simplify left and right side of the equation.
-21e=-9

We divide both sides of the equation by -21 to get e.
e=0.428571428571

See similar equations:

| b+5b=42 | | 54/3^2*6(6-3) | | 13c-52= | | 6x+33=16x+3 | | 4r-1whenr=9 | | 4.6x-12.1=10.9 | | 8r^2=18+18r | | 93-4x=4x-5 | | 4x+9=-67 | | X+5Y=2X+Y | | -9+3(7y-8)=4(-3y+3)+5 | | 4x-9=-67 | | (x/4)^2-225=(150-x/4)^2 | | m/4+6=m/3+8 | | x^4-7x^3-30x^2=0 | | 1/2r+6=5 | | 6p - 5=2p+7+7 | | 5t-18=12+3x | | 1+4i/4-i | | -7x-16=-5x | | 15p^2=20+20p | | 3y/8-9=y/8 | | 10q+3(5-2q)+4(7q+4)= | | 5x/-4=6x/8 | | 4/15z=1/10-4/9 | | 2x+1x+1x=180 | | -1+5=m-8 | | -4.90x^2-2.25x+1.92=0 | | y=1/2(8-1) | | 45-15-5(y+10)= | | x^2+0.0201x-0.0078591=0 | | 135-4x=41x+15 |

Equations solver categories